The Influence of National Culture on the Formation of Technology Alliances by Entrepreneurial Firms - Steensma, H. Kevin; Marino, Louis; Weaver, K. Mark; Dickson, Pat H. (Academy of Management Journal, 2000)
We consider the effect that national culture has on the propensity for small, independent manufacturing enterprises to (1) cooperate with other firms for technological innovation and (2) use equity ties in the formation of these alliances. Results from a five-country study indicate that national culture traits directly influence technology alliance formation and moderate the relationship between perceived technological uncertainty and alliance formation. Specifically, our results suggest that a resource dependence explanation for technology alliance formation is strongest for societies that maintain cooperative values and avoid uncertainty. A transaction cost explanation for the use of equity ties is strongest for societies that value individualism.